Malaysia unleashed - technopreneurship growth strategies for a digital era - Ahamat, Amiruddin (Penerbit UTeM Press, 2024)
This book is a deep dive into the heart of Malaysia's technopreneurial ecosystem, exploring the strategies and insights that propel businesses into the forefront of the digital revolution.